2018
DOI: 10.1589/jpts.30.347
|View full text |Cite
|
Sign up to set email alerts
|

The influences of client-centered therapy on the level of performance, the level of satisfaction of activity of daily living, and the quality of life of the chronic stroke patients

Abstract: [Purpose] The purpose of this research is to take a look at the influences of client-centered therapy on the level of everyday life performance, the level of satisfaction, and the quality of life of the chronic stroke patients. [Subjects and Methods] This research used client-centered therapy with two chronic stroke and hemiplegia patients as subjects. The therapy was carried out once a day, five times a week, for thirty minutes at a time for four weeks. Also, five kinds of training were included in the medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Both participants showed significant changes and improvement in QoL, performance, and satisfaction level. 18 In current study, 126 patients were receiving routine physical therapy treatment and survey was done to gather information and they also showed improved QoL. Population who do not have rehabilitation treatments have low level of energy and their social life is more effected by the stroke then the patients who have proper rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 87%
“…Both participants showed significant changes and improvement in QoL, performance, and satisfaction level. 18 In current study, 126 patients were receiving routine physical therapy treatment and survey was done to gather information and they also showed improved QoL. Population who do not have rehabilitation treatments have low level of energy and their social life is more effected by the stroke then the patients who have proper rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 87%
“…In organisations, secondary and tertiary institutions around the world, numerous researchers have undertaken studies on CCT on educational, vocational and personal–social concerns. A number of them (Bondestam & Lundqvist, 2020; Elliott, 2016; Hashemi Pour & Bahreinian, 2019; Jones, 2020; Park, 2018; Saad et al, 2014) found CCT to be very effective. This study assumes that CCT will, to some extent, address SH problems in tertiary institutions in Taraba State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%